A long-range cis-regulatory element for class I odorant receptor genes. Issue 1 (December 2017) - Iwata, Tetsuo; Niimura, Yoshihito; Kobayashi, Chizuru; Shirakawa, Daichi; Suzuki, Hikoyu; Enomoto, Takayuki; Touhara, Kazushige; Yoshihara, Yoshihiro; Hirota, Junji
Abstract Individual olfactory sensory neurons express a single odorant receptor gene from either class I genes residing in a single cluster on a single chromosome or class II genes spread over multiple clusters on multiple chromosomes. Here, we identify an enhancer element for mouse class I genes, the J element, that is conserved through mammalian species from the platypus to humans. The J element regulates most class I genes expression by exerting an effect over ~ 3 megabases within the whole cluster. Deletion of thetrans J element increases the expression frequencies of class I genes from the intact J allele, indicating that the allelic exclusion of class I genes depends on the activity of the J element. Our data reveal a long-rangecis -regulatory element that governs the singular class I gene expression and has been phylogenetically preserved to retain a single cluster organization of class I genes in mammals. "Each olfactory sensory neuron expresses a single odorant receptor gene from either class I or class II genes. Here, the authors identify an enhancer for mouse class I genes, that is highly conserved, and regulates most class I genes expression by acting over ~ 3 megabases within the whole cluster."